Exploring the factors shaping food recycling behaviour: a sustainable perspective - Shawal Sahid Hamid@Hussain,; Noorliana Safian,; Syamaliah Ngah,; Mohd Idham Mohd Yusof,; Farah Murni Merican,; Siti Melinda Haris, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Food waste is a pressing global issue with significant environmental, social, and economic implications. This paper aims to investigate the recycling of food waste behaviour, focusing on the relationship between social norms, cultural attitudes and public awareness. Malaysia contributes 259.82 kg per person annually to the staggering food wastage of 8.3 million metric tonnes. In this study, a qualitative content analysis research design is used. The study conducts a detailed review of studies on food waste behaviour study explores the variables in the research, categorized as dependent and independent. The dependent variable is recycling food waste behaviour, while the independent variables are public awareness, government policies and regulations, and cultural attitudes. Public awareness significantly influences community behaviour, particularly among youth, highlighting the importance of recycling food waste. Social norms also play a crucial role by embedding recycling as a daily practice. Cultural attitudes affect recycling behaviours through established norms and traditions. The study also examines the Theory of Planned Behaviour (TPB) by Ajzen (1985).